المجيئات المعيبة - مرعي, رئيفة; الدالي, عصام; إسرب, لمى (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة في مشفى الأسد الجامعي باللاذقية، في قسم التوليد وأمراض النساء في الفترة ما بين 1/1/2002 - 1/6/2003، وتضمنت (163) حالة ولادة لمجيء معيب من أصل (2384) حالة ولادة لأجنة حية مفردة بتمام الحمل. كانت نسبة المجيئات المعيبة في مشفى الأسد الجامعي باللاذقية : (6.8)%. درست كل من العوامل التالية باعتبارها عوامل مؤهبة لحدوث المجيئات المعيبة : 1- تعدد الولادات 2- سوابق ولادة مجيء معيب 3- التشوهات الرحمية. كانت نسبة الولادة المهبلية في المجيئات المعيبة (36.81)% بينما كانت نسبة الولادة بالعملية القيصرية (63.19)%. كانت نسبة الرضوض الولادية (7.36)%. كانت نسبة التشوهات الولادية المرافقة للمجيئات المعيبة (5.5)%. كانت نسبة بعض العوامل المرافقة للمجيئات المعيبة على الشكل التالي: - ارتكاز المشيمة المعيب: (2.45)%. - انفكاك المشيمة: (0.6)%. - انسدال السرر: (3.06)%. This research was conducted in AL-ASSAD University Hospital Lattakia, in Obstetrics and Gynecology Department between 1/1/2002 - 1/6/2003, on (163) abnormal presentation cases out of (2384) pregnant women who had a: single, live, at term pregnancy fetus. The rate of abnormal presentation was (6.8)%. The following factors are considered as predispose factor: (multiparity - previous abnormal presentation and uterine anomalies ...). The rate of vaginal delivery in abnormal presentation was (36.81)% while cesarean section’s rate was (63.19)%. The rate of birth truma was (7.36)%. The rate of congintial malformation was (5.5)%. The percentage of some accompaning factors: [placenta previa (1.8)% - umblical cord prolapse (3.06)% - placental abruption (0.6)%].